‘Bucket Handle’ bipedicled flap for reconstruction of large scalp defects - Dorian Hobday; Constantinos Kokkinos; Yazan Al-Ajam; Naghmeh Naderi; Norbert Kang (JPRAS Open)
Summary: Although advances in free flap surgery have allowed the reconstruction of a wide range of complex scalp defects, simpler local options continue to play a role. We describe how bipedicled or ‘bucket handle’ scalp flap with skin grafting of the donor site can be used to resurface large scalp defects of up to 15 cm x 20 cm.This retrospective case series of 11 patients describes flap outcomes, post-operative complications, pathology and patient-related outcomes collected via a questionnaire.Defect sizes ranged from 56 cm2 to 220 cm2. All 11 flaps survived with no readmissions or return to theatre. There were two minor post-operative infections. Pathologies requiring reconstruction were invasive squamous cell carcinoma involving the bone (45%), cranial bone necrosis after a cerebrovascular event (27%), trauma (9%) or cerebral malignancy (9%). Four patients (36%) underwent simultaneous cranial reconstruction with a cranioplasty plate. On an average, the patients who did not need to remain in the hospital for other reasons were discharged after two days. All patients reported subjective improvements in function post-operatively and that they were satisfied with the procedure.This study suggests that large bipedicled scalp flaps with skin graft to the donor site are reliable, with positive patient-related outcomes and few post-operative complications. This technique is well suited for reconstructing long elliptical scalp defects created after the insertion of a cranioplasty plate. This procedure provides a robust alternative to patients who are unsuitable for free tissue transfer and those who may benefit from the short operative time and quick recovery time associated with a local flap.